(untitled) (Research, Society and Development, 2021)
Covid-19 was detected in December 2019, spread worldwide, changing the way people work, especially those who are working on the front line, the nursing professionals. They had to live with the situation in the work environment and at the same time learn about the new virus. In this context, several studies began to be produced to improve the care of these professionals to patients affected by Covid-19 and provide knowledge to them. This study aimed to evaluate the knowledge of nursing professionals working in the pandemic context on the specifics of Covid-19. This is a quantitative, descriptive, cross-sectional study conducted in a hospital in Rondonópolis, MT. Reliability analysis was performed using Cronbach’s alpha. Data collection was by means of a checklist questionnaire. Fifty professionals working in the front line at Covid-19 were interviewed, being 7 nurses and 43 nursing technicians. The instrument showed high reliability, 0.885. It was noted that there is understanding about general aspects of Covid-19, such as the form of infection, signs and symptoms, diagnosis, and treatment. In summary, the interviewees demonstrated knowledge paired with the information provided in the current regulations, serving as support in the provision of care.